2005
DOI: 10.1017/s0025315405010829h
|View full text |Cite
|
Sign up to set email alerts
|

Doses of darkness control latitudinal differences in breeding date in the barnacle Semibalanus balanoides

Abstract: This paper reports the first study of breeding in the boreo-arctic barnacle Semibalanus balanoides in which latitudinal variation in timing of egg mass hardening has been examined simultaneously over the geographical scale involved, thereby excluding temporal confounding of the data. The timing of autumn egg mass hardening on the middle shore was established in 2002 and 2003 at ten stations ranging latitudinally from Trondheim (63°24′N) to Plymouth (50°18′N). To assess variation at local scale (<10 km), bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…Seasonal fluctuations in the intensity, duration, and spectral composition of light change with latitude, and act as important phenological cues for a range of marine species, sometimes in combination with temperature. Light regime thresholds likely trigger events such as reproduction and migration (Davenport et al, 2005), in addition to temperature thresholds. Thus, temperature-driven shifts in distribution and phenology of species can be constrained by the influence of the seasonality of light on photoperiod, particularly at high latitudes (Figure 4; Saikkonen et al, 2012;Sundby et al, 2016).…”
Section: Ecological Responses Across Ocean Regionsmentioning
confidence: 99%
“…Seasonal fluctuations in the intensity, duration, and spectral composition of light change with latitude, and act as important phenological cues for a range of marine species, sometimes in combination with temperature. Light regime thresholds likely trigger events such as reproduction and migration (Davenport et al, 2005), in addition to temperature thresholds. Thus, temperature-driven shifts in distribution and phenology of species can be constrained by the influence of the seasonality of light on photoperiod, particularly at high latitudes (Figure 4; Saikkonen et al, 2012;Sundby et al, 2016).…”
Section: Ecological Responses Across Ocean Regionsmentioning
confidence: 99%
“…The day-length hypothesis (Davenport et al, 2005) postulates that reproduction is dependent upon shortening day length, and that there is geographic variation in response. Extrapolation of the latitudeday of year regressions indicated that the southern limit of Semibalanus should be either in southern France or in Galicia (Davenport, 2005).…”
Section: Day-length Hypothesismentioning
confidence: 99%
“…The warm winter hypothesis has support in that temperatures above 10°C have been shown in the laboratory to inhibit reproduction (Barnes, 1958;Crisp & Patel, 1969;Barnes & Stone, 1972). More recently Davenport et al (2005) proposed that day length might set the southern geographic limit of Semibalanus.…”
Section: Introductionmentioning
confidence: 98%
“…The timing of fertilization in the barnacle Semibalanus balanoides is linked mostly to photoperiod (Crisp 1959a;Davenport et al 2005), presumably so that the embryos will be developmentally ready to be released by the time the winter-spring phytoplankton bloom begins a few months later.…”
Section: The Importance Of Temporal Scale In Observations Of Marine Imentioning
confidence: 99%
“…However, cloud cover is expected to increase as the climate changes, and this "global dimming" could alter the photoperiod that barnacles experience (Davenport et al 2005). Under these conditions, S. balanoides would be expected to undergo fertilization earlier in the year, since the perceived length of darkness would be longer.…”
Section: Potential Impacts Of Climate Change On the Timing Of Reprodumentioning
confidence: 99%